Comparative Study of the Use of Bismuth Shielding on Head Computed Tomography Scans Using Phantoms - Fernanda Stephanie Santos (Brazilian Journal of Radiation Sciences)
Computed Tomography (CT) has been one of the most used exam for radiologic diagnostic in medicine. The increase of CT is a global concern due to high doses of radiation. The dose evaluation in CT is one of many steps that can contribute for reducing patient doses. The head CT scans helps to diagnose disorders that affect the brain, including tumors, infarction, bleeding within the brain, hematoma and other diseases. The aim of this work is to compare the reduction of absorbed dose in the head CT scan with and without the use of bismuth shielding using a male and female anthropomorphic phantom model Alderson Rando.The head CT scan were done from the cervical vertebra C1 to the top of skull, in a GE CT scanner, LightSpeed VCT model, with 64 channels.Radiochromic films strips were used to evaluate the doses in the organs such as lenses, thyroid, hypophysis, spinal cord, pharynx, breasts, salivary and parotid glands.Record doses were lower with the use of bismuth shielding in both phantoms for all organs, mainly in the lenses. The analysis of noise in the image of the head central slice presented acceptable values for soft tissues, less than 1%. Dose values were significantly reduced and they suggested that the use of bismuth shielding would be a proper procedure for protection during a head CT scan.